Yearly distribution and composition of per- and polyfluoroalkyl substances (PFAS) in Luleå wastewater treatment plant - Sjöberg, Moa (Luleå tekniska universitet, Institutionen för samhällsbyggnad och naturresurser, 2023)
PFAS (per- and polyfluoroalkyl substances) are a large group of substances that are used in a large variety of products because of their unique water and dirt repellent properties. The substances are extremely persistent and can spread over large distances in groundwater, surface water, and in the air, which makes them an environmental and a health concern. A significant pathway of PFAS into the environment is through wastewater, where the usage of consumer products containing PFAS contribute to the emissions. The project was performed by analysing data of PFAS concentrations in wastewater and sludge sampled continuously during 2022 at Uddebo wastewater treatment plant (WWTP) in Luleå municipality. The aim was to evaluate the composition of PFAS compounds and their concentrations in wastewater and sludge and compare with other municipalities, to analyse how PFAS concentrations change during the existing wastewater treatment process, and to suggest strategies for future treatment of PFAS in wastewater. No significant change of the PFAS content in wastewater could be observed throughout the treatment process in Uddebo WWTP. Evaluation of the PFAS composition showed that PFOS was the most abundant substance in both water and sludge. Over the year some variations in the total PFAS concentration could be seen, which coincided with increased water flow during the snowmelt period and an operational disturbance at the treatment plant. The variations of the total PFAS concentrations in wastewater over the year were mainly caused by PFBA, PFOS and 6:2 FTS. Analysis of total oxidizable precursors in the wastewater showed that substances that can transform into more persistent PFAS are present in the incoming water to the plant to a large extent. The pilot plant designed for treatment of pharmaceuticals, including ozonation and a granular activated carbon filter, did not result in any separation of PFAS from the water. An assessment of the contribution of PFAS from landfill leachate showed that it constitutes a significant ...